2021
DOI: 10.1021/acs.est.1c00575
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mass Yields of Aqueous Secondary Organic Aerosol from Highly Substituted Phenols Reacting with a Triplet Excited State

Abstract: Biomass burning emits large amounts of phenols, which can partition into cloud/fog drops and aerosol liquid water (ALW) and react to form aqueous secondary organic aerosol (aqSOA). Triplet excited states of organic compounds ( 3 C*) are likely oxidants, but there are no rate constants with highly substituted phenols that have high Henry's law constants (K H ) and are likely important in ALW. To address this gap, we investigated the kinetics of six highly substituted phenols with the triplet excited state of 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 80 publications
5
63
0
Order By: Relevance
“…We also tested the direct photodegradation of the highly substituted ArOH by illuminating 15 μM solutions without the addition of H 2 O 2 . Three phenols (ferulic acid, syringic acid, and syringyl acetone) undergo significant direct photodecay on the timescale of our experiments (Section S2 and Ma et al, Section S4 ). We corrected the measured first-order rate constants for loss of these compounds in the presence of · OH by subtracting the first-order direct photodegradation loss.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…We also tested the direct photodegradation of the highly substituted ArOH by illuminating 15 μM solutions without the addition of H 2 O 2 . Three phenols (ferulic acid, syringic acid, and syringyl acetone) undergo significant direct photodecay on the timescale of our experiments (Section S2 and Ma et al, Section S4 ). We corrected the measured first-order rate constants for loss of these compounds in the presence of · OH by subtracting the first-order direct photodegradation loss.…”
Section: Methodsmentioning
confidence: 85%
“…Phenols are oxidized in the gas and aqueous phases to form SOA. ,, In the gas phase, phenol oxidation is primarily by · OH and proceeds through · OH addition, with SOA mass yields between 17 and 86%. ,, In the aqueous phase, oxidation of ArOH is more complex due to additional oxidants, especially the triplet excited states of organic compounds ( 3 C*). , Hydroxyl radical oxidation of ArOH in the aqueous phase also proceeds via · OH addition, with SOA mass yields that range from 59 to 105%, notably higher than for gas-phase reactions, , probably because of more efficient aqueous formation of oligomers …”
Section: Introductionmentioning
confidence: 99%
“…On a related note, a recent work (Ma et al, 2021) (Brezonik and Fulkerson-Brekken, 1998;Chu and Anastasio, 2003). The same study also estimated that reactions of phenols with high Henry's law constants (10 6 to 10 9 M atm -1 ) can be important for SOA formation in ALW, with (Ma et al, 2021). Likewise, Zhou et al (2019) reported that the direct photodegradation of acetosyringone was faster by about 6 times in the presence of M NaClO4.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 82%
“…While nitration can be an important process for producing light-absorbing organics or BrC (Jacobson, 1999;Kahnt et al, 2013;Mohr et al, 2013;Laskin et al, 2015;Teich et al, 2017;Li et al, 2020), its effect on triplet-generating aromatics has not yet been examined in detail. On a related note, a recent work (Ma et al, 2021) (Brezonik and Fulkerson-Brekken, 1998;Chu and Anastasio, 2003). The same study also estimated that reactions of phenols with high Henry's law constants (10 6 to 10 9 M atm -1 ) can be important for SOA formation in ALW, with (Ma et al, 2021).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 83%
“…The most important sources of OH in the atmospheric aqueous phase are the Fenton reaction between Fe­(II) and H 2 O 2 accounting for about 33%, the photolysis of H 2 O 2 with a contribution of about 25.5%, and the uptake of OH into the cloud droplets accounting for 21.6% out of the total source of OH . It has been shown that photolysis of nitrite and photosensitized chemistry occurring within the aerosols and cloud water can be an additional significant source of OH in the atmospheric aqueous phase. Phenolic compounds are ubiquitous in the atmospheric aqueous phase, which are of great concern related to human health and the environment. ,, Phenols can be released into the atmosphere by anthropogenic activities such as biomass and fossil fuel burning or be formed from the reaction of aromatic hydrocarbons with OH radical. , The atmospheric aging of phenols can occur in both gas phase and aqueous phase, which is known to contribute significantly to the formation of secondary organic aerosol (SOA), including brown carbon. There is increasing evidence that aqueous-phase reactions play a significant role in the chemical transformation of phenolic compounds in the atmosphere. , The oxidation of phenols in atmospheric waters is initiated by its reactions with aqueous oxidants such as OH, excited triplet states of organic matter ( 3 C*), reactive nitrogen species (RNS), and O 3 . Compared to OH-, 3 C*- or RNS-mediated aqueous aging of phenols, there are very few reports on the oxidation of phenols initiated by O 3 in atmospheric aqueous phase, and little is known about product distributions from the reaction of phenols with O 3 under different conditions.…”
Section: Introductionmentioning
confidence: 99%